Professional Skills in a Master’s Program: A View from Graduates and Employers - Velázquez-Cigarroa, Erasmo; Méndez-Cadena, María Esther; Fontalvo-Buelvas, Juan Camilo; Quintero-Romero, Dulce María; López-Velasco, Rocío (Journal of the University of Zulia, 2024)
The aim of the research was to analyze the perceptions of graduates and employers about the competencies promoted and developed in the Master’s Degree in Management for Sustainable Development (MGDS) at the Autonomous University of Guerrero (UAGro). The study was descriptive and cross-sectional and included the virtual application of questionnaires through the QuestionPro and Google Forms platforms. There was a sample of 45 graduates representing all previous generations and 14 employers who have a reach of 40 former graduate students. The results show that the ex-students (98%) are satisfied with the training received, although they pointed out areas for improvement in ethical and humanistic matters. Likewise, employers point out that the professional preparation of graduates is ideal and they have outstanding skills to fulfill their job functions. Finally, the postgraduate program presents features of quality and relevance to the context, given the presence of professors who generate multidisciplinary environments, but also thanks to the sustainability approach that is in line with current demands.